1996
DOI: 10.1111/j.1558-5646.1996.tb03580.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Size Dimorphism as a Correlated Response to Selection on Body Size: An Empirical Test of the Quantitative Genetic Model

Abstract: Abstract.-We artificially selected for body size in Drosophila melanogaster to test Lande's quantitative genetic model for the evolution of sexual size dimorphism. Thorax width was used as an estimator of body size. Selection was maintained for 21 generations in both directions on males only, females only, or both sexes simultaneously. The correlated response of sexual size dimorphism in each selection regime was compared to the response predicted by four variants of the model, each of which differed only in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
84
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 41 publications
9
84
0
Order By: Relevance
“…Although female wing size forms virtually identical clinal patterns on all three continents, parallel male clines have not evolved in the New World (Gilchrist et al 2004). In other drosophilids, the genetic correlation between male and female size is nearly one; however, the observed response in one sex to selection on the other sex lags behind predictions made by quantitative genetics (Reeve and Fairbairn 1996), suggesting that the contrast in female and male clinal patterns might not be unexpected. Larger wings could evolve either by increasing cell size or by increasing cell number.…”
Section: Discussionmentioning
confidence: 80%
“…Although female wing size forms virtually identical clinal patterns on all three continents, parallel male clines have not evolved in the New World (Gilchrist et al 2004). In other drosophilids, the genetic correlation between male and female size is nearly one; however, the observed response in one sex to selection on the other sex lags behind predictions made by quantitative genetics (Reeve and Fairbairn 1996), suggesting that the contrast in female and male clinal patterns might not be unexpected. Larger wings could evolve either by increasing cell size or by increasing cell number.…”
Section: Discussionmentioning
confidence: 80%
“…Of those mutants with sex-limited effects, even fewer exclusively affect either shape or size dimorphism (Fig.2). While some studies have been successful in artificially altering SSD of specific traits through selection (Bird & Schaffer 1972; Emlen et al 2005; Reeve & Fairbairn 1996), it is unclear whether whole trait size or simply trait shape (e.g. length) has been altered.…”
Section: Discussionmentioning
confidence: 99%
“…Selection need not directly act on body size (or morphology) to affect patterns of sexspecific plasticity in size and morphological traits (97). Selection on traits correlated with body size, either positively (such as nuptial gifts) or negatively (i.e., traits that trade-off with size, such as development time), can vary between the sexes and favor increased or decreased plasticity of one sex over the other.…”
Section: Phenotypic Plasticity In Body Size In Insectsmentioning
confidence: 99%
“…The evolution of SSD is slowed by genetic (97), phylogenetic (26), developmental (8), and/or physiological (93) constraints. For example, empirical studies have shown that heritabilities are similar between the sexes and that the between-sex genetic correlations ( r G ) are near 1.0 (because males and females share the same genes that control growth and development) (79, 98, 102).…”
Section: Introductionmentioning
confidence: 99%